Credit-Implied Equity Volatility – Long-Term Forecasts and Alternative Fear Gauges - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2014)
This study discusses how to compute and forecast long-term stock return volatilities, typically with a 5-year horizon or longer, using credit derivatives, and how such volatilities can be used in different areas ranging from the valuation of employee stock options and other long-term derivatives to the construction of market-based fear gauges in selected countries or market segments. In the empirical part of the paper I focus on the European financial sector and find the credit-implied volatilities and fear gauges to behave well. The forecasting accuracy of the credit-implied volatilities is found to be better than that of horizon-matched historical volatilities.
Keywords: G10; 330; credit default swaps; implied volatility; CreditGrades; VIX; fear gauge; long-term forecast